2008
DOI: 10.1002/j.2333-8504.2008.tb02148.x
|View full text |Cite
|
Sign up to set email alerts
|

AUTOMATED SCORING OF SPONTANEOUS SPEECH USING SPEECHRATERSM V1.0

Abstract: This report presents the results of a research and development effort for SpeechRater SM Version 1.0 (v1.0), an automated scoring system for the spontaneous speech of English language learners used operationally in the Test of English as a Foreign Language™ (TOEFL ® ) Practice Online assessment (TPO). The report includes a summary of the validity considerations and analyses that drive both the development and the evaluation of the quality of automated scoring. These considerations include perspectives on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…More and more applied linguistics and computational linguistics conferences have taken the initiative to invite or encourage the participation of researchers from the other discipline to share and debate issues of common interest. Recent collaborative efforts between applied linguists and computational linguists to build automated scoring and feedback systems have allowed some applied linguists to develop expertise in applying test validity theories to the validation of automated scoring systems (Bernstein et al, 2010;Carr and Xi, in press;Xi et al, 2008). Specialized interdisciplinary programs have also emerged to provide formal training in both language learning and assessment and computer technologies (e.g., Applied Linguistics and Computer Technologies at Iowa State University).…”
Section: Xiaoming XImentioning
confidence: 99%
See 1 more Smart Citation
“…More and more applied linguistics and computational linguistics conferences have taken the initiative to invite or encourage the participation of researchers from the other discipline to share and debate issues of common interest. Recent collaborative efforts between applied linguists and computational linguists to build automated scoring and feedback systems have allowed some applied linguists to develop expertise in applying test validity theories to the validation of automated scoring systems (Bernstein et al, 2010;Carr and Xi, in press;Xi et al, 2008). Specialized interdisciplinary programs have also emerged to provide formal training in both language learning and assessment and computer technologies (e.g., Applied Linguistics and Computer Technologies at Iowa State University).…”
Section: Xiaoming XImentioning
confidence: 99%
“…As discussed in Chapelle & Cho and Enright & Quinlan in this issue, current test validation theories provide guiding principles for the validation and evaluation of automated scoring and feedback systems (Clauser et al, 2002;Xi, 2008;Xi et al, 2008). These guiding principles translate well into a series of questions that we can ask and seek answers to in our validation and evaluation work.…”
Section: Automated Scoring Researchmentioning
confidence: 99%
“…First, some automated speech evaluation systems (e.g., the one used in the Versant speaking tests developed by Pearson) constrain the context of the utterance so that users' spoken output becomes highly predictable. Other ASE systems (e.g., SpeechRater developed by ETS) compensate for this limitation with free speech recognition by expanding the speaking construct to include pronunciation, vocabulary, and grammar, in addition to fluency (Xi, Higgins, Zechner, & Williamson, 2008). According to Xi (2010a), currently neither of these approaches "has successfully tackled the problem of under-or misrepresentation of the construct of speaking proficiency in either the test tasks used or the automated scoring methodologies, or both" (p. 294).…”
Section: Research On Automated Assessmentmentioning
confidence: 99%
“…A few researchers studied the automatic scoring of Chinese writing as well and found that computer-calculated scores by the use of latent semantic analysis (LSA) were close to human-rated scores [5]. Some scholars also explored the automated scoring of short questions [6] and speech [7,8,9,10] with multiple measures.…”
Section: Introductionmentioning
confidence: 99%